2003
DOI: 10.1016/s0968-0896(02)00323-1
|View full text |Cite
|
Sign up to set email alerts
|

Quinazolines as adenosine receptor antagonists: SAR and selectivity for A2B receptors

Abstract: We have recently reported the discovery of numerous new compounds that are selective inhibitors of all of the subtypes of the adenosine receptor family via a pharmacophore database searching and screening strategy. During the course of this work we made the unexpected discovery of a potent A 2B receptor antagonist, 4-methyl-7-methoxyquinazolyl-2-(2′-amino-4′-imidazolinone) (38, CMB 6446), which showed selectivity for this receptor and functioned as an antagonist, with a binding K i value of 112 nM. We explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…Subsequent treatment with acetylacetone gave the corresponding pyrimidine (47); however, nonoptimized treatment of the substituted 4-methylquinazolyl-2-guanidines with mesityl oxide failed to give the corresponding dihydropyrimidine under the conditions specified in the literature (45). Analysis of the activities of the analogues in the quinazoline class against the TR enzyme (Table 4) revealed that some changes in the substitution on the quinazoline ring could be tolerated without significant loss of activity (IC 50 was observed when the dihydropyrimidine moiety (X ϭ A) was replaced by a more stable pyrimidinol/pyrimidinone (X ϭ B) (compound 16), pyrimidine (X ϭ C) (compounds 17 and 18), or guanidine (X ϭ D) (compounds 19 and 20) moiety (Table 4). The early SAR results suggested that the dihydropyrimidine moiety is essential for TR-inhibitory activity; however, the microsomal metabolism assessment suggests that this is a chemically unstable moiety that is rapidly metabolized.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent treatment with acetylacetone gave the corresponding pyrimidine (47); however, nonoptimized treatment of the substituted 4-methylquinazolyl-2-guanidines with mesityl oxide failed to give the corresponding dihydropyrimidine under the conditions specified in the literature (45). Analysis of the activities of the analogues in the quinazoline class against the TR enzyme (Table 4) revealed that some changes in the substitution on the quinazoline ring could be tolerated without significant loss of activity (IC 50 was observed when the dihydropyrimidine moiety (X ϭ A) was replaced by a more stable pyrimidinol/pyrimidinone (X ϭ B) (compound 16), pyrimidine (X ϭ C) (compounds 17 and 18), or guanidine (X ϭ D) (compounds 19 and 20) moiety (Table 4). The early SAR results suggested that the dihydropyrimidine moiety is essential for TR-inhibitory activity; however, the microsomal metabolism assessment suggests that this is a chemically unstable moiety that is rapidly metabolized.…”
Section: Resultsmentioning
confidence: 99%
“…26 Synthetic efforts on 2-guanidino quinazolines as adenosine receptor antagonists add on the picture of actual quinazoline research fields. 27 …”
Section: Resultsmentioning
confidence: 99%
“…6) proved to be quite potent and selective at the A 2B AR subtype. 85 The development of potent and selective A 2B AR antagonists for use in humans therefore appears particularly beneficial and may further increase knowledge of the role of these receptors in physiological and pathological conditions.…”
Section: A 2b Adenosine Receptorsmentioning
confidence: 99%